URGENSI PENDIDIKAN KEWIRAUSAHAAN DALAM MENGHASILKAN WIRAUSAHAWAN MUDA DARI PERGURUAN TINGGI - Salam, Hasni Abdul (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This article reviews the urgency of entrepreneurship education in universities. The study was carried out through a process of analyzing various sources from literature and journals related to entrepreneurship. Discussion result shows that entrepreneurship education is very important to be applied in universities in any department to produce graduates with entrepreneurial mentality who is able to open employment opportunities to support the progress of the country's economy.